High-resolution palaeohydrological reconstruction of central Italy during the Holocene. (March 2019) - Marchegiano, Marta; Francke, Alexander; Gliozzi, Elsa; Wagner, Bernd; Ariztegui, Daniel
The endorheic nature of Lake Trasimeno in combination with its position in central Italy makes it a relevant site to better constrain spatial differences in Holocene climatic variability in the Mediterranean area. Herein, we present a high-resolution ostracod record from the Holocene section of an 8.59-m-long sedimentary core, which is compared with historical data to distinguish anthropogenic and climatic signals. The occurrence, abundance and vanishing of ostracod species are directly controlled by lake-level variations, which are in turn related to global and regional climatic changes (i.e. moisture variations). The total organic carbon content as well as observed lithological changes provide additional information about Lake Trasimeno's hydrological and trophic conditions in the past. Most important variations have been identified at ca. 10, 000 cal. yr BP, when the lacustrine basin changed from a temporary to a permanent waterbody (from Sarsicypridopsis aculeata to Candona angulata association). The highest lake level and the total absence of ostracods occur at around 9000 cal. yr BP. The recorded humid phase persisted up to ca. 4200 cal yr BP since when a lake-level decreasing trend started and continued until the present day ( Candona angulata, Cyprideis torosa and Darvinula stevensoni associations). The frequency of changes in the relative abundance of the main species shows centennial variations (i.e. C. angulata, C. torosa and Darvinula stevensoni ). As historical evidences yield that human interventions to control the lake level remained unsuccessful in the past, Lake Trasimeno records an almost pristine climatic signal during most of the Holocene, which is quite unusual in the highly populated Mediterranean area.